Introduction of an electronic patient record (EPR) improves operation note documentation: the results of a closed loop audit and proposal of a team-based approach to documentation. Issue 4 (2nd December 2019) - Aldoori, Joanna; Drye, Naomi; Peter, Mark; Barrie, Jenifer
Abstract : An operation note is a medicolegal document. The Royal College of Surgeons (RCS) of England's Good Surgical Practice 2014 (GSP) sets out 19 points an operation note should include. This study aimed to assess if the introduction of an electronic patient record (EPR) improved the quality of general surgical operation notes. An annonymised retrospective case note review of general surgical operation notes was undertaken over five separate time periods. The first cycle consisted of periods 1 (prior to EPR implementation), 2 (1 week after EPR) and 3 (4 weeks after EPR). Period 4 was a reaudit 2 weeks after the initial results were presented at the local governance meeting. The cycle was then closed with period 5; 1 year after EPR implementation. A comparison was across all 5 time periods for compliance with the RCS guidelines and with subanalysis of the individual categories. 250 operation notes were reviewed during five time periods. Compliance improved by almost 19% (p=0.0003) between periods 1 and 5. Eleven of the 19 points (57.9%) over the audit period achieved 100% compliance post-EPR compared to 0% prior. Poor compliance were noted in the categories of antibiotic use, venous thromboembolism prophylaxis and estimated blood loss (noting that these are often documented in the anaesthetic record and/or WHO checklist). EPRs do not guarantee compliance with GSP. We propose that GSP standards need to be updated to reflect the modernisation of medical records and a team-based approach with multimodality input sources would achieve better patient records and patient care.